Attitudes towards offensive advertising: Malaysian Muslims' views - Ernest Cyril, de Run; Muhammad Mohsin, Butt; Fam, Kim-Shyan; Jong, Hui Yin (Emerald Group Publishing Limited, 2010)
Results indicate that those high on religiosity differ on the nature and manner of controversial advertisements from those of low religiosity. Malay Muslims when compared on their degree of religiosity differ in terms of their evaluation of offensive nature of advertisement. More important they differ more on the reason that make these advertisement offensive compared to the nature of the products.